An Opportunity: Growing of Financial Technology to Stimulate Sharing Economy in East Java - Alfiandi Imam Mawardi (Journal of Economics, Business, and Government Challenges, 2018)
This paper analyzes the phenomenon of financial technology starts tochange conventional financial institution for helping economic development, which the financial technology more likely start-up company is the innovative solution of funding on this country. Financial technology on online-based business offers new opportunities, new investment trends and new funding resources such as lending and capital rising, wealth management and insurance, payment and financial research. I apply generalized method of moment approach on startup company data on financial technology that shows business models and the result shows that financial technology can synergy with financial institution will increase the sharing economy in East Java. Under a competitive industry, financial technology should improve their accountability, accessibility, and reliability to persuade other start-up businesses to growth up together. This paper explains what existing financial technology business model to help start-up business in Indonesia today and how financial technologies to realize good sharing economy in this East Java.